Method of separation of polydisperse particles in plasma of radio-frequency discharge - Batryshev, D.G.; Ramazanov, T.S.; Gabdullin, M.T.; Dosbolayev, M.K.; Orazbayev, S.A. (Recent Contributions to Physics, 2014)
In this work the method of separation of polydisperse dust particles in plasma of radio-frequency capacitive discharge is considered for obtaining of monodisperse and fine particles. The fundamental difference of proposed separation method from existed separation methods is that the equipotential field of plasma is used as a separation instrument. The simplicity of technology allows obtaining separated monodisperse and fine particles of different materials. The monodisperse nano- and microparticles with average sizes of 600 nm and 5 µm were obtained by developed separation method of polydisperse particles in plasma of radio-frequency capacitive discharge. The separation method of polydisperse particles is carried out by the special form of bottom electrode of radio-frequency capacitive discharge with electric trap, which allows controlling equipotential field of plasma of radio-frequency capacitive discharge. Thus, the fine particles of silica and alumina were obtained by controlling plasma equipotential filed and its parameters. The analysis of obtained samples was examined by electron scanning microscope Quanta 3D 200i (FEI company, USA) form morphology, chemical composition. The particle size distribution graphs were constructed by graphical and mathematical calculations.